Role of Na+/K+-ATPase in natriuretic effect of prolactin in a model of cholestasis of pregnancy - Abramicheva, P. A.; Balakina, T. A.; Bulaeva, O. A.; Guseva, A. A.; Lopina, O. D.; Smirnova, Olga V. (Biochemistry-Moscow, 2017)
Participation of Na+/K+-ATPase in the natriuretic effect of prolactin in a cholestasis of pregnancy model was investigated. The Na+/K+-ATPase activity in rat kidney medulla, where active sodium reabsorption occurs, decreased in the model of cholestasis of pregnancy and other hyperprolactinemia types compared with intact animals. This effect was not connected with the protein level of α1- and β-subunits of Na+/K+-ATPase measured by Western blotting in the kidney medulla. Decrease in Na+/K+-ATPase activity in the kidney cortex was not significant, as well as decrease in the quantity of mRNA and proteins of the α1- and β-subunits of Na+/K+-ATPase. There were no correlations between the Na+/K+-ATPase activity and sodium clearance, although sodium clearance increased significantly in the model of cholestasis of pregnancy and other hyperprolactinemia groups under conditions of stable glomerular filtration rate measured by creatinine clearance. We conclude that the Na+/K+-ATPase is not the only mediator of the natriuretic effect of prolactin in the model of cholesta- sis of pregnancy.
CRIS-Team Scopus Importer:2023-04-20
Keywords: cholestasis of pregnancy; kidney; Na; natriuresis; prolactin; rat